Improved Blind Multiuser Detection Algorithm Based on Minimum Output Energy - 刘婷 张立毅 陈雷 (Transactions of Tianjin University, 2012)
Based on minimum output energy, an improved blind multiuser detection algorithm is proposed by the use of Hopfield neural network. Compared with traditional algorithms, the proposed algorithm does not need the circuit for constraints. The resources are greatly saved and the complexity is reduced as well. The simulation results show that the performance of the improved algorithm is similar to that of the optimal multiuser detection algorithm which is not suitable for the mobile station. Compared with the traditional gradient blind multiuser detection algorithm, the convergence speed of the improved algorithm is quickened.